2009
DOI: 10.1021/am900474h
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Microporous Layers on Titanium

Abstract: Microporous layers on titanium (Ti) are formed by chemical treatment in highly concentrated alkaline media, and their properties and growth mechanism are examined using electrochemical techniques, in situ resistometry, scanning electron microscopy (SEM), grazing-incident X-ray diffraction (GIXRD), and glow discharge optical emission spectroscopy (GD-OES). Chemical treatment in a 5 M aqueous KOH solution yields results superior to those from the same treatment in a 5 M aqueous NaOH solution, while a 3 M aqueous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…Additionally, similar results on the effect of ionic radius in hydrothermal reactions using NaOH and KOH were reported. Moreover, Tanaka et al., compared the electrochemical properties of Ti wires which were chemically treated by immersion in highly concentrated alkaline media . The authors showed that chemical treatment in NaOH and KOH solutions resembles a general corrosion process.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Additionally, similar results on the effect of ionic radius in hydrothermal reactions using NaOH and KOH were reported. Moreover, Tanaka et al., compared the electrochemical properties of Ti wires which were chemically treated by immersion in highly concentrated alkaline media . The authors showed that chemical treatment in NaOH and KOH solutions resembles a general corrosion process.…”
Section: Introductionsupporting
confidence: 71%
“…There are a vast number of reports on the preparation of TiO 2 ‐based nanostructures with controllable morphologies that can be produced by the hydrothermal method . Generally, the reported works on hydrothermal growth of TiO 2 on Ti foil have focused on the morphology and electrochemical properties of TiO 2 nanostructured films, but there are only a few studies on the influence of different hydrothermal alkaline solutions on the TiO 2 photoelectrochemical properties. For instance, Sikhwivhilu et al .…”
Section: Introductionmentioning
confidence: 78%
“…Tanaka et al . [29] only compared the surface topography of Ti specimens after their immersion in 5 M NaOH and 5 M KOH solutions at 80°C for 1, 6, 12 and 20 h. However, wettability (by using contact angle goniometry) of NaOH- or KOH-treated titanium surfaces has never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Tas and Bhaduri (26) were the first to soak Ti sheets in a 5 M KOH solution at 60°C for 24 h and 600°C heating for 1 h in air, followed by coating these alkali-modified surfaces with an apatitic calcium phosphate layer by using a supersaturated SBF. The microporous layer formed in the 5 M KOH solution were found to develop faster and thicker under anodization with superior to the analogous layer prepared in the 5 M NaOH solution by Tanaka et al (27). Cai et al (21) applied alkali treatment with immersion of cpTi discs into KOH solutions at concentrations of 4, 6, 8, and 10 M at 600°C for 24h followed by heat treatment at 600°C for 1h.…”
Section: Discussionmentioning
confidence: 98%